1981
DOI: 10.4141/cjas81-091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Vicine on the Productive Performance of Laying Chickens

Abstract: of dietary vicinc on thc productivc pcrfirrrnance of laving chickcns. Can. J. Anim. Sci. 6l: [157][158][159][160][161] Experiments were conducted to study the effects of dietary vicine [2.6-diamino-4,5-dihydroxy pyrimidine-5 (B-D-glucopyranoside)l on feed consumption. egg and yolk weight. egg production. egg f'ertility and hatchability. in vitro hemolysis of red blood cells. plasma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 3 publications
2
19
2
1
Order By: Relevance
“…In agreement with our results, Robblee et al (1977), Muduuli et al (1981), andFru-Nji et al (2007) reported no differences in feed consumption between the control and FB diets. In contrast, Laudadio and Tufarelli (2010) reported decreased feed intake, and Magoda and Gous (2011) reported increased feed intake with increased FB inclusion.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…In agreement with our results, Robblee et al (1977), Muduuli et al (1981), andFru-Nji et al (2007) reported no differences in feed consumption between the control and FB diets. In contrast, Laudadio and Tufarelli (2010) reported decreased feed intake, and Magoda and Gous (2011) reported increased feed intake with increased FB inclusion.…”
Section: Resultssupporting
confidence: 82%
“…Muduuli et al (1981) demonstrated that vicine consumption reduced egg weight and increased erythrocyte hemolysis. According to Muduuli et al (1981) vicine may act in following three ways: reduces the amount of precursor material available to the granulosa cells, by damaging granulose cells and hence their activity, or by destroying the ovum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be hypothesized that vicine causes the production of small yolk which results in the production of small eggs. Vicine may act in the following ways: by reducing the amount of precursor material available to the granulosa cells; by damaging the granulosa cells, and hence their activity; or by destroying the ovum (Muduuli et al, 1981). Wyburn et al (1965) suggested that the granulosa cells of the yolk may be involved in the transport of the large quantities of precursor material required to form the yolk and that it may be actively involved in yolk synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Serum protein concentration was proposed to be an indicator for reflecting the adverse effect of legume seeds on growth and laying performance (Wyckoff et al, 1983). In another study, Muduuli et al (1981) stated that 1% of vicin in the diet for laying hens didn't change blood plasma protein and increased plasma lipid level (P< 0.05).…”
Section: Discussionmentioning
confidence: 99%